สภาพการจัดการแข่งขันเทนนิสอาชีพของลอนเทนนิสสมาคมแห่งประเทศไทย - ณัฐพงษ์ อุไรลักษมี (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This research aimed to study the state of professional tennis tournament management of The Lawn Tennis Association of Thailand and also to compare the results of management resources of Professional tennis tournament of The Lawn Tennis Association of Thailand. Theories of management functions including planning, organizing, leading and evaluating and management resources including personnel, financial and budget, competition and equipment and facilities were employed. The samples were 86 people comprising tournament directors, tournament supervisors, referees and chair umpires. A purposive sampling was employed. Questionnaires were utilized to collect the data and the Percentage, Mean and Standard deviation were presented. Comparative results of management resources were discussed by using one way ANOVA (F-test). Furthermore, the differences were analyzed in pair by using LSD. Research findings 1. The overall state of professional tennis tournament management of The Lawn Tennis Association of Thailand is at high level with the following management resources including Man, Money, Management and Material. 2. The comparative results of the three professional tennis tournament showed a statistical significant difference at the .05 for Man and Material.